Comparison of Dexmedetomidine Plus Bupivacaine Versus Bupivacaine Alone for Spinal Anesthesia in Patients Undergoing Abdominal Hysterectomy - Ahmad, Mirza Sijeel; Haider, Syed Aftab; Adnan, Ahmad; Sultan, Atqua; Saleemi, Muhammad Saleem; Khan, Umer (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the peri-operative analgesic efficacy and quality of block by adding Dexmedetomidine as an adjuvant to Bupivacaine for spinal anaesthesia in patients undergoing abdominal hysterectomy. Study Design: Comparative cross-sectional Study. Place and Duration of Study: Anesthesia Department, Nishtar Hospital, Multan Pakistan, Jan to Jun 2019. Methodology: A total of 100 women aged 30-65 years, who were planned for abdominal hysterectomy due to benign causes, and having ASA) status I-II were included. The patients were divided into two equal groups. In Group-B, 12.5mg of 0.5% hyperbaric diluted in 3ml normal saline was administered for induction of spinal anaesthesia. In contrast, in Group-B+D, 10µg Dexmedetomidine and 12.5mg 0.5% hyperbaric Bupivacaine diluted in 3ml normal saline were given. Time of sensory and motor block onset, total duration of the block, and analgesia were noted. Results: The mean time of sensory and motor onset was significantly lower in the Group-B+D. The total duration of sensory block was 181.6±31.6 minutes in Group-B versus 345.2±23.5 minutes in Group-B+D (p-value <0.001). The total duration of the motor block was 142.9±8.6mins in Group-B versus 314.2±8.9mins in Group-B+D (p-value <0.001). Total analgesia duration was 129.4±8.3mins in Group- B versus 263.8±13.7mins in Group-B+D (p-value <0.001). A total of 2.54±0.35mg of rescue analgesia were required in Group- B versus 1.42±0.51mg in Group-B+D (p-value <0.001). Conclusion: The use of Dexmedetomidine as an adjuvant to Bupivacaine for spinal anaesthesia shortens the onset and prolongs the duration of sensory and motor block and the total duration of analgesia.